Buah naga (hylocereus polyrhizus) dan buah bit (beta vulgaris) terhadap peningkatan kadar hemoglobin - Rohanah Rohanah; Ratumas Ratih Puspita; Rafika Dora Wijaya; Rita Dwi Pratiwi; Jelika Avelia Hareva (Holistik Jurnal Kesehatan, 2023)
Background: Adolescents experience menstruation, have unhealthy eating habits, and cannot provide enough nutrients needed by the body to maintain Hb formation. If this happens for a long time, it will reduce Hb levels and cause anemia. So it can be seen that young women are the group most at high risk of experiencing anemia.Purpose:  To determine the effectiveness of giving dragon fruit and beetroot juice on hemoglobin levels in anemic adolescents.Method: A quasi-experimental design with a two-group pre-test and post-test design. We collected data through Hb examination before and after the intervention—the sample of 60 early adolescent participants who experienced anemia. The collecting sample was by purposive sampling.Results: Statistical test using the Wilcoxon test obtained an average hemoglobin level after administration of Dragon Fruit juice 13.03 ± 1.27g/dl and an average hemoglobin level after administration of beetroot juice 12.03 ± 0.32g/dl and difference in the difference in hemoglobin levels after administration of Dragon Fruit juice and Beet Fruit juice 1 ± 0.95 g/dl. Statistical test results obtained p-value = 0.001, ɑ: 0.05) p-value (0.001) < (0.05), its means that there is an effect of giving dragon fruit and beetroot juice to anemic adolescents.Conclusion: Dragon fruit and beetroot juice can increase Hb levels in anemic adolescents.Suggestion: For early adolescents is essential to prevent anemia, including consuming foods high in hemoglobin, such as dragon fruit and beetroot.Keywords: Adolescent; Anemia; Beetroot; Dragon Fruit; HaemoglobinPendahuluan: Remaja putri pada dasarnya mengalami menstruasi dan memiliki perilaku kebiasaan makan yang tidak sehat dan tidak mampu mencukupi zat makanan yang di butuhkan oleh tubuh untuk proses sistensis pembentukan Hb. Jika terjadi dalam waktu yang lama akan mengakibatkan kadar Hb berkurang dan menyebabkan anemia. Maka dapat dilihat bahwa remaja putri merupakan kelompok yang paling berisiko tinggi mengalami anemia.Tujuan: Mengetahui efektivitas pemberian jus buah naga dan buah bit terhadap kadar hemoglobin pada remaja anemia.Metode: Quasi eksperiment dengan rancangan two group pre-test and post-test design, data yang dikumpulkan dengan cara pemeriksaan Hb sebelum dan sesudah intervensi. Jumlah sampel sebanyak 60 partisipan remaja awal yang mengalami anemia diambil dengan tehnik purposive sampling.Hasil: Uji statistic dengan menggunakan uji Wilcoxon diperoleh rata-rata kadar hemoglobin sesudah pemberian jus Buah Naga 13,03 ± 1,27g/dl dan rata-rata kadar hemoglobin sesudah pemberian jus Buah Bit 12,03 ± 0,32g/dl dan perbedaan selisih kadar hemoglobin sesudah pemberian jus Buah Naga dan jus Buah Bit 1 ± 0,95g/dl. Hasil uji statistic diperoleh nilai (p-value=0,001, ɑ: 0,05) nilai p (0,001)< (0,05), sehingga dapat disimpulkan bahwa ada pengaruh pemberian jus buah naga dan buah bit terhadap peningkatan kadar HB  pada remaja anemiaSimpulan: Jus buah naga dan buah bit dapat meningkatkan kadar Hb pada remaja anemia.Saran: Bagi remaja awal penting untuk mencegah anemia salah satunya dengan mengkonsumsi zat makanan yang tinggi haemoglobin seperti buah naga dan buah bit.